Raman and TEM studies of carbon nanotubes produced by bimetallic catalysts system - Sulaiman, Yusram; Buang, Nor Aziah; Abd. Majid, Zaiton; M. Sanip, Suhaila; Ismail, Ahmad Fauzi (2005)
Studies were carried out on the use of various bimetallic catalyst systems for the production of carbon nanotubes (CNTs) by thermal decomposition of acetylene (C2H2). The pyrolysis of C2H2 was carried out at 700 Â°C. The CNTs synthesized were examined by Raman spectroscopy and transmission electron microscopy (TEM). Both analyses confirmed the presence of multi-walled carbon nanotubes (MWNTs) for all the bimetallic catalyst systems investigated. Raman spectroscopy shows that the Co-Ni supported catalyst produced CNTs with the highest IG/ID value. TEM was conducted to investigate the quality and nature of the CNTs produced. TEM observations show that the CNTs produced are multi-walled and the residual catalyst particles are located inside the tubes of the CNTs. Energy-disperse X-ray analysis (EDAX) confirmed that the residual catalysts in the CNTs are in the four of alloy.